Analysis of the filtrate quality from discontinously operated rapid filters - Zielina, Michał (Instal, 2021)
There are reports in the literature suggesting the possibility of a deterioration of the filtrate quality after interrupting the operation of a rapid filter for several hours and restarting it without prior backwash. The theoretical reasons for this phenomenon are analysed in this paper. The results of experimental research at one of Krakow’s filter stations are presented. The filters were taken out of operation for a few hours twice. The first time, shortly after backwash, when the bed was still slightly colmated, and the second time, after a longer period of time, when the bed was already largely filled with sludge. The tests showed a complete lack of deterioration of the filtrate quality after the first removal of the filter from service. The second time, a slight deterioration in turbidity removal efficiency was observed for a short period of time compared to the efficiency before the filter was taken out of service. At the same time, large and sustained decreases in the removal efficiency of total particle number and suspended solids concentration were observed. This phenomenon was caused by smaller decreases in the removal efficiency of finer particles and larger, longer lasting decreases in the removal efficiency of coarser particles. The observations showed a possibility of safe disconnection of filters with a small degree of collimation and a risk of disconnection of filters at a later stage of their exploitation.